Preparation of short cytosine-modified oligonucleotides by nicking enzyme amplification reaction - Ménová, Petra; Hocek, Michal (Chemical communications (Cambridge, England), 2012)
A method for enzymatic production of short (10-20 nt) cytosine-modified oligonucleotides was developed by nicking enzyme amplification reaction using Vent(exo-) polymerase, Nt.BstNBI nicking endonuclease and 5-substituted dCTP derivatives. The methodology including isolation was scaled up to nanomolar amounts and was proved to be suitable for production of diverse base-modified short single-stranded oligonucleotides (inaccessible by other enzymatic methods) that are of potential interest as labelled primers or functionalized aptamers.
Keywords: DNA Primers; techniky amplifikace nukleových kyselin; DNA Breaks, Single-Stranded; Nucleic Acid Amplification Techniques; Oligonucleotides; Deoxyribonucleases, Type II Site-Specific; restrikční endonukleasy typu II; jednořetězcové zlomy DNA; DNA primery; oligonukleotidy; Deoxycytosine Nucleotides; deoxycytosinnukleotidy